Peran Majelis Ulama Indonesia Kabupaten Enrekang dalam Penyadaran Masyarakat Menunaikan Zakat, Infaq, dan Sedekah - Syandri Syandri; Azwar Iskandar (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
The aim of this research is to understand the role of Majelis Ulama Indonesia (Ulama Council of Indonesia, MUI) in promoting the fulfilment of zakat, infaq, and sedekah among Muslims in Enrekang Regency. This paper applied descriptive method with qualitative approach. Findings reveal that the MUI of Enrekang Regency has implemented several strategic steps regarding its’ advising and guiding roles pertaining to the fulfilment of zakat, infaq, and sedekah. Those steps are: (1) Advocating the collection of zakat, infaq, and sedekah funds, (2) educating the community about zakat, infaq, and sedekah gradually, (3) maintaining good cooperation with Badan Amil Zakat Nasional (BAZNAS) in the regency, and (4) delivering targeted explanation on the importance of the zakat of profession. Keywords: Infaq, Majelis Ulama Indonesia Enrekang, sedekah, and zakat.